Implementasi Perancangan Virtual Private Network (VPN) dan Pembatasan Media Access Control Address pada PT Pegadaian Kantor Area Palembang - Kharisma Pangestu (Institute of Information Technology and Social Science (IITSS), 2021)
The development of information technology and computer networks has become a primary requirement in supporting company operational activities. PT Pegadaian has an internal network that can only be accessed through a cable network and internal switches to maintain data security. However, the limited number of cable devices and employee work mobility are obstacles to operational efficiency. This study aims to implement a Virtual Private Network (VPN) over a Wireless Local Area Network (WLAN) by implementing Media Access Control (MAC) address restrictions and WPA2-PSK security. The method used is the Network Development Life Cycle (NDLC) which includes the stages of analysis, design, simulation, implementation, monitoring, and management. The results of the study show that all registered user devices successfully connected to the VPN network via WLAN. In addition, user restrictions through MAC address filtering have been proven to improve network security. Thus, the implementation of a WLAN-based VPN with MAC address and WPA2-PSK security has successfully increased the flexibility and security of internal network access at PT Pegadaian's Palembang Area Office.